Clonal selection in the human Vδ1 T cell repertoire indicates γδ TCR-dependent adaptive immune surveillance - Davey, Martin S; Willcox, Carrie R; Joyce, Stephen P; Ladell, Kristin; Kasatskaya, Sofya A; McLaren, James E; Hunter, Stuart; Salim, Mahboob; Mohammed, Fiyaz; Price, David A; Chudakov, Dmitriy M; Willcox, Benjamin E (Nature communications, 2017)
γδ T cells are considered to be innate-like lymphocytes that respond rapidly to stress without clonal selection and differentiation. Here we use next-generation sequencing to probe how this paradigm relates to human Vδ2neg T cells, implicated in responses to viral infection and cancer. The prevalent Vδ1 T cell receptor (TCR) repertoire is private and initially unfocused in cord blood, typically becoming strongly focused on a few high-frequency clonotypes by adulthood. Clonal expansions have differentiated from a naive to effector phenotype associated with CD27 downregulation, retaining proliferative capacity and TCR sensitivity, displaying increased cytotoxic markers and altered homing capabilities, and remaining relatively stable over time. Contrastingly, Vδ2+ T cells express semi-invariant TCRs, which are present at birth and shared between individuals. Human Vδ1+ T cells have therefore evolved a distinct biology from the Vδ2+ subset, involving a central, personalized role for the γδ TCR in directing a highly adaptive yet unconventional form of immune surveillance.
Keywords: hypervariabilní oblasti; dospělí; dárci tkání; proliferace buněk; CX3C Chemokine Receptor 1; Complementarity Determining Regions; Phenotype; biologické markery; Biomarkers; Adult; Tissue Donors; Cytotoxicity, Immunologic; Receptors, Antigen, T-Cell, gamma-delta; imunitní dozor; buněčné klony; Immunologic Surveillance; buněčná diferenciace; lidé; cytotoxicita imunologická; antigeny CD27; receptory antigenů T-buněk gama-delta; Genetic Variation; Tumor Necrosis Factor Receptor Superfamily, Member 7; interleukin-15; Cell Proliferation; Cell Differentiation; Clone Cells; fenotyp; genetická variace; CX3C chemokinový receptor 1; Interleukin-15; Humans